European Development Cooperation In Between the Local and the Global - Hoebink, Paul (EADI, 2010)
Official Development Assistance, or foreign aid, disbursed by the EU member states reached record levels in 2008, when several member states raised their assistance considerably, while some of the new member states became donors again. This definitive study analyses a wide range of aspects of European development cooperation, covering, among others, some hotly debated issues such as the Economic Partnership agreements, development policy coherence and the participation of civil society organisations in negotiations with the European Union. The contributors offer valuable new insights into the established aid instruments such as food aid, support for energy projects in Africa and security-related development assistance in the programmes of some smaller European donors, as well as an overview of these new donor programmes. They also discuss the role of local and regional authorities in development cooperation in the Netherlands, Germany and Spain. This title is available in the OAPEN Library - http://www.oapen.org.